2009
DOI: 10.1074/jbc.m808404200
|View full text |Cite
|
Sign up to set email alerts
|

Mapping of the C3d Ligand Binding Site on Complement Receptor 2 (CR2/CD21) Using Nuclear Magnetic Resonance and Chemical Shift Analysis

Abstract: Complement receptor 2 (CR2, CD21) is a cell membrane protein, with 15 or 16 extracellular short consensus repeats (SCRs), that promotes B lymphocyte responses and bridges innate and acquired immunity. The most distally located SCRs (SCR1-2) mediate the interaction of CR2 with its four known ligands (C3d, Epstein-Barr virus gp350, interferon-␣, and CD23). Inhibitory monoclonal antibodies against SCR1-2 block binding of all ligands. To develop ligand-specific inhibitors that would also assist in identifying resi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
22
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 51 publications
2
22
0
Order By: Relevance
“…Thermodynamic studies of CR2-ligand interactions have yielded slightly differing results ( Table 2). As reported previously, the CR2-C3d interaction has been described as either being a two-site or a single site binding interaction (17,48). Our ITC data best fit a two-mode binding model with a weaker K d of 160 M and a tighter interaction of 0.13 M. This K d value is fairly close to the previously determined K d value from a surface plasmon resonance-based biophysical study (17).…”
supporting
confidence: 77%
See 2 more Smart Citations
“…Thermodynamic studies of CR2-ligand interactions have yielded slightly differing results ( Table 2). As reported previously, the CR2-C3d interaction has been described as either being a two-site or a single site binding interaction (17,48). Our ITC data best fit a two-mode binding model with a weaker K d of 160 M and a tighter interaction of 0.13 M. This K d value is fairly close to the previously determined K d value from a surface plasmon resonance-based biophysical study (17).…”
supporting
confidence: 77%
“…Human IFN␣ for NMR titrations and ITC studies was generated using the pMAL expression system in E. coli as described previously (48). Ampicillin-resistant colonies were used to start overnight cultures that were expanded to 1 liter and grown at 37°C until an A 600 of 0.3 was obtained.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, they appear to still contend that the CR2(SCR2):C3d interface seen in the cocrystal is correct. The cocrystal structure indicated that the side chain of R83 in SCR2 was the central player in the extensive hydrogen-bond network bridging SCR2 to C3d, and it is true that both the mutagenic (36) and chemical shift perturbation (43) data support the involvement of R83 in binding SCR2 to C3d. In the 2005 study by Hannan et al (36), it was hypothesized that a cluster of four C3d residues that formed an acidic channel located immediately adjacent to the area visualized as the contact area for SCR2 in the cocrystal structure could provide the direct interaction site for SCR1 that for unknown reasons was absent in the cocrystal structure.…”
Section: Discussionmentioning
confidence: 90%
“…A more recent study using solution NMR spectroscopy and chemical shift perturbation mapping analysis suggested involvement of amino acids in binding to C3d that are located in both CCP1 and CCP2 and the intermodular linker. 42 However, caution should be exercised in interpreting the NMR data because of possible alosteric affects involved in binding, 43 possibly mediated by intermodular electrostatic interactions. 5 Our study is based on the high-resolution crystal structure of C3d-CR2(CCP1-2) 7 and provides predictions under the assumption of correctness of the crystal structure and a working hypothesis that explains the experimental mutations.…”
mentioning
confidence: 99%